Properties of oriented strand board (OSB) from mixed species of Mahang and Lundai / Wan Mohd Nazri Wan Abdul Rahman …[et al.] - Wan Abdul Rahman, Wan Mohd Nazri; Othman, Ahmad Fauzi; Rosman, Norhafizah; Kasim, Jamaludin (Universiti Teknologi MARA Cawangan Pahang, 2007)
Efficient and economical utilisation of various bio-based materials is an effective way to improve forest management. Oriented strand board (OSB) from fast growing and lesser-known tropical species in this study seems to have good potential for various structural and exterior applications. However, this potential will depend on further research and improvements in the physical and mechanical properties of the OSB. The main objective of the study is to develop and determine the properties of oriented strand board from mixed tropical species (lesser-known and fast growing) as a raw material in the manufacturing of OSB. Species like Ludai and Mahang were found in this study to be a suitable alternative raw material since the results showed that most of the treatments met the minimum requirements of mechanical and physical properties. It can be deduced from this study, that mixing Ludai and Mahang from fast growing tropical species had improved the board performance as compared to their single species. All of the mechanical and physical properties evaluated met the requirements of EN 310:1994, EN 317:1994 and EN 319:1994 for general purpose OSB.